NTFPs in the Bolivian Amazon: socio-economic impact in view of institutional deficiencies - Stoian, D.; Gottwald, C.; Ruíz, S.; Jong, W. de; Becker, M.; Bojanic, A. (2001)
There is not abstract is available for this publication.